Late Sodium Current And If Inhibition: Targets of New Antianginal Drugs - Das, Uzzwal Kanti; Ahsan, Syed Ali; Haque, KMHS Sirajul; Ahmed, Md. Khurshed (University Heart Journal, 2008)
Ischaemic heart disease is the common cause of mortality and morbidity in developed countries despite tremendous development in treatment in last two decades. Recently cardiac Ion Channels and other cellular components have become the target of research for new cardiovascular drugs. A number of new drugs have emerged after pre-clinical and clinical trials. Ranolazine by inhibiting late sodium current in ventricular cardiomyocytes and ibavradine by inhibiting If current in pacemaker cells have emerged as effective new antianginal drugs. Both are discussed in this review article. Key Words: Late Sodium current (IPNa), Diastolic tension, After depolarization, If current, heart rate. (University Heart Journal 2007; 3 : 75-78)